Innovation of Small Medium Micro Business Governance (MSME) Resilience Post-Covid-19 Pandemic in Bandung City - Caesar, Muhammad Ridwan; Haryadi, Rudi (Budapest International Research and Critics University, 2022)
In 2020 the Covid-19 pandemic began to enter Indonesia and had a significant impact on the stagnation of the Indonesian economy. The real impact is directly felt by business actors with micro, small and medium scale in the city of Bandung. Even the government itself has predicted that in its implementation it is very difficult, economic growth in Indonesia could decline to 0.4 percent. This was taken based on industry data and business actors who were affected by the Covid-19 pandemic on the domestic macro economy which became very heavy. The purpose of this study is to find out innovations in managing MSMEs that are resilient to disasters after the Covid-19 pandemic in the city of Bandung. The research stages include identifying MSMEs affected by the Covid-19 Pandemic, reviewing government policies related to MSME governance during the Covid-19 Pandemic to further map the modeling of Disaster Resilient MSME governance.